Simulative Analysis of Column Mobility Model for Proactive and Reactive Routing Protocols in Highly Dense MANET - Kour, Satveer; Sarangal, Himali; Singh, Manjit; Singh, Butta (Recent Advances in Computer Science and Communications, 2024)
One of the most promising fields of research in recent years is Mobile Ad Hoc Networks (MANET). The well-known advantages of the internet for specific types of applications lead to the fact that it is a wireless ad-hoc network. As a result, such networks can be utilized in circumstances where no other wireless communication infrastructure is present. A MANET is a network of wireless devices without any centralized control. A device can directly communicate with other devices using a wireless connection. For nodes that are located far from other nodes, multi-hop routing is employed. The functionality of route-finding is performed by routing protocols. The mobility model creates the movement pattern for nodes. This article discusses early research to address concerns about performance indicators for MANET routing protocols under the Column Mobility Model (CMM). Moreover, we discuss concerns regarding the designs of the related work, followed by the designed CMM model on the behavior of routing protocols.
Keywords: routing protocols